História da genética no Brasil: as contribuições de Friedrich Gustav Brieger para o melhoramento do milho (1938-1966) - Cunha, Solange (2010)
The German scientist Friedrich Gustav Brieger made important contributions for the genetics of vegetables. He leaded the group of ESALQ (Superior School of Agriculture Luiz de Queiroz) situated in Piracicaba, São Paulo, Brazil. The aim of this dissertation is to discuss Briegers ideas concerning the improvement of mays trying to detect if he brought anything new concerning this subject from 1938 to 1966. Besides that, it will try to find if there were any significant change in ESALQ after Brieger s arrival at ESALQ. This dissertation contains an introduction and three chapters. Chapter 1 provides an overview of Brieger career and a general view of the history of ESALQ. Chapter 2 deals with the Brazilian s agricultural schools. Chapter discusses about Brieger, contributions to the improvement of mays. Chapter 4 presents some final remarks on the subject. This study led to the conclusion that Brieger s influence on ESALQ was significant in several respects such as: changes in the curriculum, the introduction of practical classes, the building of researchers as well as the results of his own research on the improvement of mays